The Effect of Social Performance to the Profitability of Islamic Banks - Himmatul Kholidah (TIJAB (The International Journal of Applied Business), 2018)
This study aims to investigate the effect of social performance to the profitability of Islamic banks. The research method used is quantitative approach with multiple regression analysis. The data in this research have four variables: Mudharabah-Musyarakah Financing, Qardh Financing and Zakah as dependent variables and Net income as independent variable. The result shows that only zakah has significantly positive effects on the net income, but Mudharabah-Musyarakah and Qardh Financing have insignificant effects on the net income of Islamic commercial bank. On the other hand, Mudharabah-Musyarakah Financing, Qardh Financing and Zakah simultaneously have significant effects on the net income of Islamic commercial bank.